The Role of the Prosecutor's Office in Stopping the Prosecution of Domestic Violence Criminal Cases Based on the Prosecutor's Regulation of the Republic of Indonesia Number 15 of 2020 (Labuhanbatu State Prosecutor's Study) - Rico Marthin Sihombing; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon; Abdul Hakim (International Journal Labs, 2023)
The role of the Prosecutor's Office has become a hot topic in the legal world in Indonesia today because of the many cases and legal problems that are applied by prioritizing a sense of justice and for the justice-seeking community as well as for law enforcers restorative justice approaches in enforcement and application efforts to obtain meaning from the purpose of the law made. Because restorative justice is a legal necessity that is captured by law enforcement officials. We can see in the development of existing laws and regulations, each law enforcement agency is competing to take part and play a role in implementing the principles of restorative justice according to their respective duties and authorities. Starting from the Police, Prosecutor's Office, Supreme Court, and Prisons, in this case the Prosecutor's Office issued Attorney General Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice.